Brood care and male behavior in queenless Acromyrmex subterraneus brunneus (Hymenoptera: Formicidae) colonies under laboratory conditions - Camargo, Roberto S. [UNESP]; Forti, Luiz C. [UNESP]; Lopes, Juliane F. S.; Andrade, Ana Paula P. [UNESP] (My University, 2006)
In this study we describe and quantify the brood care performed by workers in queenless colonies of the leaf-cutting ant Acromyrmex subterraneus brunneus. Fifteen behavioral acts were recorded in the three colonies studied. The behavioral repertoire of males was more limited, with only four behavioral acts being observed: feeding through workers, collecting staphylae and self-feeding, mutual grooming between adults (worker-males), and self-grooming. Males were also found to be able to collect food (staphylae or fungal hyphae) from the fungus garden and to feed themselves, not requiring workers for this activity. This study contributes to a better understanding of the basic biology of leaf-cutting ant colonies, with the description and quantification of the activities performed by the members of a colony in a situation of the loss of the fertile caste.
Keywords: Behavioral acts; Leaf-cutting ants; Males; Queenless colony; Acromyrmex subterraneus brunneus; Atta; Formicidae; Fungi; Hymenoptera